Social mobility: Is there a benefit of being English in Scotland? - Maarten Van Ham; Allan Findlay; David Manley; Peteke Feijten (European Regional Science Association (ERSA), 2010)
A number of powerful forces have produced uneven opportunities for occupational advancement in Scotland. Edinburgh as capital of a devolved nation, hub for financial service activities and regional head office location for many public sector bodies boasts many of the characteristics that one would expect to find in a region offering good opportunities for rapid social and occupational mobility. One would certainly anticipate that this is true compared with the urban areas in Scotland associated with de-industrialisation and economic restructuring. However, there are also many individual level factors that influence success in the labour market. This paper seeks to unpick the complex relationships between individual success, migration, ethnicity, country of birth and place of residence in Scotland. We do this using longitudinal census data linking individual records from the 1991 and 2001 Censuses obtained via the Scottish Longitudinal Study. From the data we create logistic regression models assessing the probability that individuals in social classes 3 and 5 move upwards, and that individuals in social classes 1 or 2 maintain their position. Particular attention is given to the labour force experience of English-born residents, whom the cross sectional literature suggests are more likely to achieve high occupational status than their Scottish counterparts.
Keywords: J24; J61; J62; R23; 330; Escalator Region; Social Class; Social Mobility; Longitudinal data; Scotland